2021
DOI: 10.22541/au.161755023.36264823/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant communities and potential native phytoremediator species in petroleum hydrocarbon-polluted desert systems

Abstract: This paper reported the recovery of desert plant communities after twenty years of oil-derived hydrocarbon contamination in desert habitats of Kuwait, caused by the First Gulf War (1990 – 1991). The hypothesis that certain native desert plant species can tolerate weathered oil-polluted soils with oil breakdown products (i.e., polycyclic aromatic hydrocarbons ( PAHs)) and have the potential to function as bioindicators and phytoremediator species for oil-polluted soil was tested. A field survey of 200 quadrat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This research was conducted at the Al-Burgan oil field located in the southeast of Kuwait ( Figure 1 ). This site is currently damaged and is subject to the restoration and revegetation program [ 9 ]. It was an oil-extraction site before it was destroyed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was conducted at the Al-Burgan oil field located in the southeast of Kuwait ( Figure 1 ). This site is currently damaged and is subject to the restoration and revegetation program [ 9 ]. It was an oil-extraction site before it was destroyed.…”
Section: Methodsmentioning
confidence: 99%
“…The contaminated sites are currently included in the restoration and remediation program. Previous studies found that some native plants in Kuwait can survive and grow over hydrocarbon-polluted soils, including the perennial shrubs Haloxylon salicornicum and Rhanterium eppaposum , and the perennial sedge Cyperus conglomeratus [ 9 ]. The regrowth of native desert plants may also vary from one site to another, depending on the extent of disturbance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%